Perancangan Dan Realisasi Prototype Sistem Transfer Daya Listrik Nirkabel Untuk Mengisi Baterai Handphone - Sherly Puspita Rahman; Mas Sarwoko; Zulfi . (Jurusan Teknik Elektro Universitas Andalas, 2013)
Ongoing trends in standardized mobile phone charger is charging process with user-friendly wireless power transfer that eliminates the cable connection between the charger and the phone. Wireless power transfer provides convenience in mobile phone battery charging, do not have to hassle with wires and plugs, simply put the phone on the pad. The research design and realize a prototype of a wireless power transfer system for charging mobile phone batteries. This research used high frequency transformer 12 V 25 kHz, the primary coil (20 turns, diameter 9 cm), the secondary coil (36 turns, diameter 9 cm), rectifier and filter and regulator. The result showed that the device and the circuit is designed to perform charging mobile phone batteries with maximum distance required to produce a voltage of 5 volts at the input terminal of mobile phone batteries is as far as 2 cm. In addition, the time required to perform a full battery charge until the phone is 60 minutes with constant charging rate.Keywords: magnetic Induction, Resonance, Electromagnetic, Wireless power transfer AbstrakTren yang sedang berlangsung dalam standarisasi charger handphone adalah proses pengisian user-friendly dengan transfer daya nirkabel yaitu menghilangkan sambungan kabel antara charger dan handphone. Transfer daya nirkabel memberikan kemudahan dalam pengisian baterai handphone, tidak perlu repot dengan kabel dan colokan, cukup meletakkan handphone pada bantalan. Penelitian ini merancang dan merealisasikan sebuah prototype sistem transfer daya nirkabel untuk pengisian batere handphone. Dalam penelitian ini digunakan high frequency transformator 12 V 25 kHz, primary coil (20 lilitan, diameter 9 cm), secondary coil (36 lilitan, diameter 9 cm), rectifier and filter dan regulator. Dari hasil penelitian diperoleh bahwa alat dan rangkaian yang dirancang dapat melakukan pengisian batere handphone dengan jarak maksimum yang dibutuhkan untuk menghasilkan tegangan 5 Volt pada terminal masukan batere handphone adalah sejauh 2 cm. Selain itu, waktu yang diperlukan untuk melakukan pengisian batere handphone hingga penuh adalah 60 menit dengan laju pengisian konstan.Keywords: magnetic Induction, Resonance, Electromagnetic, Wireless power transfer